Effect of Acacia mangium Willd plantations on the natural regeneration of a savanna - Reyes-Moreno, Giovanni; Darghan, Aquiles Enrique; Ramírez, Wilson Ariel; Garibello, Juan Camilo (Revista de Ciencias Agrícolas, 2024)
Introducing alien species into natural ecosystems can generate important changes in water quality and supply level, ecosystem services, and biodiversity. Different results have been found with the appearance of alien species that contemplate both high invasion risks and opportunities to form new ecosystems that permit a new path toward restoration. This research aimed to analyze the contribution of Acacia mangium Willd. plantations for ecological restoration using both spectral instruments and conventional sampling to calculate the abundance or frequency of species appearances. Two analyses were conducted on four plant covers (an active plantation, a felled forest, and a gallery forest edge). The analysis was of a spectral type, evaluating two vegetation indices and their relationship with the Berger-Parker biotic dominance index (D); the vegetation indices were NDVI (the normalized difference vegetation index) and CVI (the chlorophyll vegetation index). The statistical methodologies involved spatial regression modeling to relate diversity and spectral indices and a permutational multivariate analysis of variance for the variables associated with regeneration. We found that felled plantations have a higher degree of similarity to gallery forests in terms of spectral indices and diversity when compared to active plantations. The composition and abundance of species of natural regeneration in plantations differ significantly from both regeneration in forests and regeneration in savannas.